2011
DOI: 10.1364/ol.36.002215
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the principal component algorithm in phase-shifting interferometry

Abstract: We recently presented a new asynchronous demodulation method for phase-sampling interferometry. The method is based in the principal component analysis (PCA) technique. In the former work, the PCA method was derived heuristically. In this work, we present an in-depth analysis of the PCA demodulation method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 3 publications
0
53
0
Order By: Relevance
“…Thus, we will present first the procedure to demodulate the isoclinic fringe pattern using the proposed PCA algorithm and, afterwards, we will make use the information obtained from the isoclinics fringe pattern to demodulate the isochromatics one. However, we will first summarize the PCA method for phase demodulation [10].…”
Section: Theoretical Foundationmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, we will present first the procedure to demodulate the isoclinic fringe pattern using the proposed PCA algorithm and, afterwards, we will make use the information obtained from the isoclinics fringe pattern to demodulate the isochromatics one. However, we will first summarize the PCA method for phase demodulation [10].…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…From construction, X C is symmetric and it is always possible to find a linear transformation A, (a KK  matrix) that diagonalizes it, so that the transformed covariance matrix ·· T YX  C A C A is diagonal. In the literature, the linear transformations A is also known as Karhunen-Loève or Hotelling transforms [10].…”
Section: Pca Analysis Of Phase Shifted Interferogramsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method requires filtering out the DC term, but it does not require normalizing the fringe patterns. In [4][5] we have shown that a sequence of phase-shifted fringe patterns free from harmonics can be expressed as a linear combination of two orthonormal signals. Therefore, any phase-shifted interferogram sequence can be described using a twodimensional vector subspace.…”
mentioning
confidence: 99%